GAMIFICATION IN TEACHING INNOVATION: PERCEPTION OF TEACHER ADAPTATION WITH THE ORGANISM-RESPONSE STIMULUS PARADIGM - Ani Rakhmanita; Paramitha Kusumawardhani; Desy Tri Anggarini (Jurnal Education and Development, 2023)
The use of gamification in teaching innovation provides hope to involve students, motivate in their learning study. Most of the previous studies examined the success of gamification for students. However, there are few studies that examine teacher perceptions in adapting the application of gamification. In this study, we used a qualitative approach to delve deeper into the opportunities and barriers teachers feel in implementing learning gamification. The results showed that some teachers could see the benefits of gamification in attracting students' interest in learning and creating more interactive learning. From the other side, some teachers find gamification challenging in its application. The perceived barriers for teachers to use gamification are lack of time in preparing gamification, lack of knowledge about gamification, and inapposite class arrangements for game educatin activities. There must be a stimulus from related organizations in overcoming this problem, for example by providing teacher training on the benefits of applying gamification to encourage the response of teachers in implementing gamification learning.